Advances in technology for complex custom feed material treatment at Noranda - M. Bédard; G. Kachaniwsky (Canadian Institute of Mining, Metallurgy and Petroleum, 1991)
"The Noranda Continuous Smelting Process at the Home smelter was commissioned in March 1973. The ability of the process to handle a wide variety of feed materials and a steady stream of technical innovations in recent decades has served to maintain the Home as an efficient and versatile custom smelter. This paper reviews recent technological development and capabilities in areas such as sampling and preparation of secondary and complex materials, as well as the smelting and related environmental control issues. Future trends and improvements are also addressed.IntroductionThe Noranda Home smelter commenced operations in 1927. It was originally designed to treat 910 tonnes per day of copper concentrates and ores coming from the new Home mine site. In the 19305, the company opened its doors to other mines in northwestern Quebec. Treatment of feed materials on a custom basis has, therefore, always been an important factor in the operation of the Home smelter. Throughout the years, the Home gradually increased its custom smelting capacity, while maintaining its production from the Home mine. By the early 1950s, 65% of the materials processed was from outside customers, and by 1974, this figure had increased to more than 85% . With the closure of the Home mine in 1976, the company extended its smelting operations beyond ore and concentrate, and began to treat more scrap metals and residues rich in copper and precious metal content.Corresponding with the ever-changing pattern of feed sources, the Home smelter has adopted technological improvements to meet new and challenging business conditions. The technology of the original smelter of 1927has been completely replaced over the years in the quest for improvement. One of these major changes occurred in 1973 with the start-up of the Noranda Process Reactor. This extremely efficient smelting system has been exploited to treat a wide variety of copper and precious metal (PM) containing custom materials. This paper reviews recent developments and improvements achieved at the Home smelter, in the receiving, sampling and treatments of copper and PM scrap and secondaries, with particular emphasis on the development of new technology and equipment in complex feed materials treatment."